Medical humor and its role in the process of social perception of the disease (and of the patient) - Plapler, Helio; Carelli, Fabiana Buitor (Research and Humanities in Medical Education, 2021)
According to evolutionary theory, humor is a psychological coping mechanism - a ploy that the human brain uses for conflict resolution. This study aims to investigate, through an autoethnographic approach based on one of the author’s (HP’s) personal experience as a patient and as a doctor, and through theoretical elaboration, how humor can be understood, in its textual form, to improve the relationship between physicians, other healthcare personnel, and patients. Furthermore, it evaluates how humor can reduce the anguish produced by the daily contact with disease, or at least can minimize some of the existential consequences of illness. This paper is a conceptualization of humor, anecdote, and "chiste" (Witz) to understand why and how humor is perceived as a means of fostering closeness, understanding and even emotional protection of those involved in the healing process.